Self‐Reported Moral Emotions and Physical and Relational Aggression in Early Childhood: A Social Domain Approach. Issue 1 (27th October 2018) - Jambon, Marc; Smetana, Judith G.
Abstract : This study examined discrepancies between 4‐ and 7‐year‐olds' ( n  =   135; M age   =   5.65) self‐reported affect following hypothetical moral versus social‐conventional transgressions and their associations with teacher‐rated physical and relational aggression concurrently and 9‐months later. Negative emotion ratings in response to prototypical moral transgressions were not associated with children's aggression. When transgressions were described as no longer prohibited by rules and authority figures, children reporting more negative affect in response to moral as compared to conventional violations were less physically aggressive at Wave 1 and showed relative and mean‐level declines in physical aggression over time. Relational aggression was not associated with self‐reported emotions. Findings indicate the importance of distinguishing between types of transgressions and forms of aggression in studying moral emotions.